Tunable luminescence in Pr3+ single-doped oxyfluoride glass ceramic and fibers. Issue 13 (8th March 2022) - Sun, Yongsheng; Wu, Minbo; Tian, Shuhang; Shi, Zhenguo; Lun, Zhenjie; Jiang, Qingquan; Zhao, Yajing; Chen, Dongdan; Xiong, Puxian; Yang, Zhongmin
Abstract : Tunable luminescence from red to white in Pr 3+ single-doped oxyfluoride glass and glass ceramic. Abstract : Compared with conventional white light emitting diodes, white lasers are highly desired for application in visible light communication due to their higher modulation bandwidth and light output power. However, the generation of white lasers in a single monolithic material constitutes a significant challenge due to its exacting requirements in the sophisticated design for simultaneous red, green, and blue oscillation. Herein, through a facile strategy, the design and preparation of a single monolithic material (the Pr 3+ single-doped transparent glass ceramic (GC)) for emission color manipulation and white light generation are reported. By controlling the growth of 5–30 nm KYF4 nanocrystals in the glass matrix, the local field environment of Pr 3+ evolves from an amorphous glass matrix to KYF4 nanocrystals, resulting in the emission color tuning from red via warm white to cold white. Impressively, the GC heat-treated at 520 °C for 2 h exhibits enhanced blue emission intensity which is approximately two orders of magnitude larger than that of glass. The feasibility of the target crystal growth in the glass matrix is validated via molecular dynamics simulations. In addition, a GC fiber with bright white light emission is successfully constructed. This work of tunable multicolor emission and white light generation from the Pr 3+ single-doped GC opens up a new avenue for the development of modulated white light GC fiber lasers for application in future visible light communication.